CONSUMERISM THE SHAME OF MARKETING IN NIGERIA. CHALLENGES TO CORPORATE PRACTICES - Daniel Ogechukwu, Ayozie (British Journal of Marketing Studies, 2014)
Is it legitimate that consumers should make their dissatisfactions known? Do consumers in Nigeria ever have any chance to complain about defective products? Are producers using God’s name to certify that their products can be sold here on earth and in heaven? Defective products are becoming more evident, and producers are denying all the defective products they manufacture. With consumers greater education and sophistication, they are increasingly demanding for their rights and power. ICT has made it much more easier. They are asking for their rights to safety, information, choice and hearing, unlike in the past. This when consumers raise their voices in protest against unsafe or adulterated products, when government official investigate illegal deals by both businessmen and the legislatures (oil subsidy and power supply probes – Otedola and Farouk Lawal), when protests emanate from our various campuses of tertiary institutions or our streets as a result of the increase in the pump price of fuel and kerosene, or failure of business to clear up the environment, all are complaining that business and those who run or supervise it is a nuisance to the consumers and do not take the consumers into confidence in affairs that concern them. This paper discusses the historical origin of consumerism, the causes, the factors contributing to the rise in Nigeria, its growing importance and the various measures that the government, individuals, organizations, journalists, and the marketer’s specific measures to react to increasing consumerism in Nigeria. It concludes by looking at the future of consumerism in Nigeria and what actions organizations needed to take to react to it positively. Many companies are trading in the intrinsic values of the brand. Consumer complaints is part of business, is part of business because they have positive effects for the organisation and their products, as it is a way by which wayward businesses and organisations are made aware of their lapses, and can begin to right the wrongs spotted out by the consumers. Customers and consumers are the kings, queens, princes and princesses of business, are sovereign and must be treated excellently well and fairly, to enable the companies to maintain their profitability, market share and loyalty. Ayozie (2012), Akpanenua (1999) declared that the consumer entity in Nigeria is hapless, hopeless and helpless. To him consumer sovereignty sounds fairly fallacious and folly. Consumerism will answer this.